2015
DOI: 10.1103/physrevb.91.045107
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of magnetic frustration in FeSe epitaxial films onSrTiO3

Abstract: The effects of electron doping and phonon vibrations on the magnetic properties of monolayer and bilayer FeSe epitaxial films on SrTiO3 have been studied, respectively, using first-principles calculations with van der Waals correction. For monolayer FeSe epitaxial film, the combined effect of electron doping and phonon vibrations readily leads to magnetic frustration between the collinear antiferromagnetic state and the checkerboard antiferromagnetic Néel state. For bilayer FeSe epitaxial film, such magnetic f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 48 publications
2
27
1
Order By: Relevance
“…Presuming (based on bulk FeSe) that FeSe provides a charge-neutral 1UC overlayer, the van der Waals (vdW) interaction may play a significant role in the interlayer bonding. Liu et al 22 reported that the distance between the top Se atom of first unit cell and the TiO 2 termination plane of the substrate is about 5.56Å when accounting for the vdW interaction, which would be consistent with the reported experimental value 5.5Å 2 . With this value, d S =2.66Å.…”
Section: A Structure Of the Simulation Cellsupporting
confidence: 84%
See 1 more Smart Citation
“…Presuming (based on bulk FeSe) that FeSe provides a charge-neutral 1UC overlayer, the van der Waals (vdW) interaction may play a significant role in the interlayer bonding. Liu et al 22 reported that the distance between the top Se atom of first unit cell and the TiO 2 termination plane of the substrate is about 5.56Å when accounting for the vdW interaction, which would be consistent with the reported experimental value 5.5Å 2 . With this value, d S =2.66Å.…”
Section: A Structure Of the Simulation Cellsupporting
confidence: 84%
“…20 Shanavas and Singh (SS) found that both O vacancies in the STO substrate and excess Fe over the monolayer can provide high levels of electron doping 21 . A somewhat different viewpoint arises from evidence that doped electrons accumulate at the interface was presented by Liu et al 22 Se vacancies were considered by Berlijn et al 23 , who observed unanticipated character of anion vacancies, behaving more as hole donors than electron donors.…”
Section: Introductionmentioning
confidence: 99%
“…Although this is a minimal representation of the substrate STO, our results reasonably reproduce previous calculations that use thicker STO substrates. 14,17,18,22 The planer lattice constant a is set to the STO parameter ∼3.9Å. The vertical heights of Fe and Se above the TiO 2 are relaxed in the CB-AFM state (as summarized in Ta- ble I of the Supplementary Information), and then held fixed during the spin-spiral calculations.…”
Section: Resultsmentioning
confidence: 99%
“…Although the energy difference between the CB-and CL-AFM states is found to be reduced by electron doping due to the substrate, the CL-AFM state remains more stable at reasonable doping levels. 14,17,22 Moreover, there is no experimental evidence for longrange magnetic order in either bulk or monolayer FeSe -recent inelastic neutron scattering experiments 24 have found that CB-AFM and CL-AFM correlations coexist even at low excitation energies in the bulk -suggesting that a quantum paramagnetic state with strong fluctuations between the CB-AFM and CL-AFM states might also exist in the monolayer system. Furthermore, it has been suggested that a nematic paramagnetic state resembling the observed bulk FeSe nematic state is a result of a near degeneracy between the CB-AFM and CL-AFM states.…”
mentioning
confidence: 99%
“…However, no Fermi surface reconstruction induced by spin density wave was observed in monolayer FeSe/STO but in mutlilayer FeSe/STO in ARPES experiments [12]. The recent first-principles calculations proposed that the magnetic order was strongly frustrated in monolayer FeSe/STO with 2J 2 ≈ |J 1 | [51]. Another issue is the sign of J 1 .…”
Section: The Effective Pairing Interactionsmentioning
confidence: 97%